A New Approach to Calculate the Velocity of Interdendritic Fluid Flow during Solidification Using Etched Surface Height of Actual Metal Ingot - Zibing Hou; Zhiqiang Peng; Qian Liu; Zhongao Guo; Hongbiao Dong (Metals, 2021)
Macrosegregation remains one of main defects affecting metal materials properties, which is mainly caused by interdendritic fluid flow during solidifying. However, as for controlling actual specific segregation, it is still difficult to effectively measure or simulate this kind flow instead of pure fluid flow, especially in complex casting processes of high-grade materials. Herein, a new method for obtaining velocity magnitude and direction of interdendritic fluid flow during metal solidifying is proposed from boundary layer and standard deviation obtained by measuring etched surface heights of the actual ingot and using statistical principles. Taking continuous casting bloom of GCr15 bearing steel as an example, it is indicated that the calculated velocity magnitudes under different sides and superheats can be explained by process features and, hence, solidification mechanism. The velocity magnitude and fluctuation are higher on the inner curve side and under low superheat. Meanwhile, it is found that the fluctuation extent of secondary arm spacing is more relevant with interdendritic fluid flow, although its magnitude is mainly determined by the cooling rate. Moreover, on the basis of the calculated velocity directions and magnitudes, there is a positive correlation between segregation area ratio and the effective ratio between interdendritic flow velocity and growth velocity especially in the equiaxed grain zone, which corresponds with classic macrosegregation formation theory. The above findings and comparison with other results demonstrate the validity of the new approach, which can obtain the magnitude and the direction of interdendritic fluid velocity for two or three-dimensional multiscale velocity distribution by tailoring measuring length and numbers.